Next-Generation Sequencing in the Understanding of Kaposi’s Sarcoma-Associated Herpesvirus (KSHV) Biology - Strahan, Roxanne (Viruses, 2016)
Non-Sanger-based novel nucleic acid sequencing techniques, referred to as Next-Generation Sequencing (NGS), provide a rapid, reliable, high-throughput, and massively parallel sequencing methodology that has improved our understanding of human cancers and cancer-related viruses. NGS has become a quintessential research tool for more effective characterization of complex viral and host genomes through its ever-expanding repertoire, which consists of whole-genome sequencing, whole-transcriptome sequencing, and whole-epigenome sequencing. These new NGS platforms provide a comprehensive and systematic genome-wide analysis of genomic sequences and a full transcriptional profile at a single nucleotide resolution. When combined, these techniques help unlock the function of novel genes and the related pathways that contribute to the overall viral pathogenesis. Ongoing research in the field of virology endeavors to identify the role of various underlying mechanisms that control the regulation of the herpesvirus biphasic lifecycle in order to discover potential therapeutic targets and treatment strategies. In this review, we have complied the most recent findings about the application of NGS in Kaposi’s sarcoma-associated herpesvirus (KSHV) biology, including identification of novel genomic features and whole-genome KSHV diversities, global gene regulatory network profiling for intricate transcriptome analyses, and surveying of epigenetic marks (DNA methylation, modified histones, and chromatin remodelers) during de novo, latent, and productive KSHV infections.